2019
DOI: 10.3390/polym11081253
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Lignocellulosic Biomass as Performance Improver for Bituminous Materials

Abstract: Lignocellulosic biomass has gained increasing attention as a performance modifier for bituminous material due to the vast amount available, its low cost and its potential to improve the durability of pavement. However, a comprehensive study concerning both the binder and mixture performance of modified bituminous material with lignocellulose is still limited. This research aims to evaluate the feasibility of applying lignocellulose as bitumen modifier by rheological, chemical and mechanical tests. To this end,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Meanwhile, the close results in high frequencies showed that the negligible effect in low-temperature performance of test binders with lignin. This finding supports past works conducted by Wang [ 47 ]. By comparison, lignin from wood chips had a slight improvement in high-temperature performance than that of lignin from corncobs.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Meanwhile, the close results in high frequencies showed that the negligible effect in low-temperature performance of test binders with lignin. This finding supports past works conducted by Wang [ 47 ]. By comparison, lignin from wood chips had a slight improvement in high-temperature performance than that of lignin from corncobs.…”
Section: Resultssupporting
confidence: 94%
“…The fatigue life (N ƒ ) results reflect that the high strain applied to the bitumen binders reduced the fatigue life regardless of whether the lignin was used and whatever the sources of lignin were. The higher value of the cycles to fatigue (N ƒ ) is, the worse fatigue resistance the test binder owns [ 47 ]. According to Figure 6 , Pen60/70 was responsible for the higher cycles and the application of lignin reduced the values of N ƒ at both strain levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lignin, one of the most abundant organic substances, can be used in a variety of applications in daily life (Alinejad et al, 2019; Wang, Cai, Zhang, Xu, & Yu, 2019). As a recalcitrant component in plants, however, lignin not only plays a vital role in strengthening plant structure (Su et al, 2019) but also regulates the plant litter decomposition rate because it is difficult to degrade and surrounds labile litter components in the cell wall, preventing their release (Melillo, Aber, & Muratore, 1982; He et al, 2016).…”
Section: Introductionmentioning
confidence: 99%